Photofission of 238U with bremsstrahlung in wide interval of values of the boundary energy - V. O. Zheltonozhsky; A. M. Savrasov; V. А. Plujko; O. M. Gorbachenko; K. M. Solodovnyk (Ядерна фізика та енергетика)
In experiments for photofission of 238U with bremsstrahlung, the isomeric yield ratios for 133Xe at the end-point energies Ee = 6.25, 14.5 and 18 MeV and for 135Xe at Ee = 6.25, 12.5 and 14.5 MeV were measured. Isomeric yield ratios were obtained taking into account the contribution from beta-decay of isobaric nuclei to the yields of investigated isotopes. Average angular moments of investigated fission fragments were determined using the statistical model of decay.